Psychological and social predictors of motorcycle use by young adult males in New Zealand - Reeder, A.I.; Chalmers, D.J.; Marshall, S.W.; Langley, J.D. (Social science & medicine (1982), 1997)
Motorcycle riding is a significant cause of serious injuries to young males. Little is known about the psychological and social characteristics of these riders, despite such knowledge being potentially important for the targeting of appropriate injury prevention interventions. Using problem-behaviour theory to broadly guide and structure the research, the present study focused on identifying predictors of motorcycle riding. Previous research investigating differences between riders and nonriders has tended to be inconclusive, methodologically limited, and lacking in explicit theoretical foundations. The present research was based on the birth cohort enrolled in the Dunedin Multidisciplinary Health and Development Study (DMHDS), a comprehensive New Zealand longitudinal study of health, development, attitudes, and behaviours. Logistic regression models were built using prior measures of health risk behaviour, other psychological and social factors, and motorcycle riding history as potential predictors of any motorcycle use at the age of 18 years. The strongest predictors were early motorcycle riding, including illegal on-road driving at age 13 (OR 4.0; 95% CI 1.7, 9.1), below average reading skills (OR 2.4; 95% CI 1.3, 4.6) and fighting in a public place at age 15 (OR 2.9; 95% CI 1.2, 6.9). It was of particular interest that this profile tended to fit less well those subgroups of riders with greatest exposure to on-road motorcycle driving. Although based on small numbers, this finding was consistent with earlier cross-sectional research that linked casual and unlicensed driving with less protective motorcycling opinions and behaviours. Some implications for injury prevention and public policies regarding motorcycling are discussed. In particular, stricter enforcement of present licensing regulations and stronger penalties for their violation could help to reduce the number of less responsible riders.